Manajemen Sumber Daya Pendidik dalam Meningkatkan Kinerja: (Studi Kasus di Universitas Nahdlatul Ulama Kalimantan Timur) - Baequni Baequni (BADAN PENERBIT STIEPARI PRESS, 2025)
Educator performance is a determining factor in the quality of higher education because it directly influences the quality of learning, research, and community service. This study aims to analyze the practice of educator resource management at Nahdlatul Ulama University of East Kalimantan (UNU Kaltim) in improving lecturer performance. The research method used a qualitative case study approach with non-participant observation techniques and literature review. Data analysis was conducted using the Miles, Huberman, and Saldana model through the stages of reduction, presentation, and drawing conclusions validated by technical triangulation. The results show that educator resource management at UNU Kaltim is implemented through needs planning, recruitment, capacity development, performance evaluation, and retention. This implementation has an impact on improving the quality of learning through the use of digital technology, increasing national publications, and lecturer involvement in community service programs. However, obstacles still arise such as the limited number of lecturers with doctoral degrees, minimal research funding, and demands for digital literacy. This study demonstrates the need for competency development strategies, expanding collaboration, and strengthening the research culture to optimize the performance of the three pillars of higher education.